Robustness tests for public transport planning - Friedrich, Markus; Müller-Hannemann, Matthias; Rückert, Ralf; Schiewe, Alexander; Schöbel, Anita (OpenAccess Series in Informatics, 2017)
The classical planning process in public transport planning focuses on the two criteria operating costs and quality for passengers. Quality mostly considers quantities like average travel time and number of transfers. Since public transport often suffers from delays caused by random disturbances, we are interested in adding a third dimension: robustness. We propose passengeroriented robustness indicators for public transport networks and timetables. These robustness indicators are evaluated for several public transport plans which have been created for an artificial urban network with the same demand. The study shows that these indicators are suitable to measure the robustness of a line plan and a timetable. We explore different trade-offs between operating costs, quality (average travel time of passengers), and robustness against delays. Our results show that the proposed robustness indicators give reasonable results.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Delays; Line planning; Passenger-orientation; Robustness measure; Timetabling